Physicochemical analysis of matured goat milk cheeses marketed in supermarkets in Guayaquil, Ecuador - Urgiles Galarza , Yenifer Fernanda; Holguín Bajaña, Marcos Vicente; García Moncayo, María Guadalupe (ECOAgropecuaria. Revista Científica Ecológica Agropecuaria, 2024)
Thanks to the high biological value provided by matured goat milk cheeses and taking as important the easy digestibility compared to other cheeses, the characterization of the nutritional quality of cheeses related to protein and dry matter was chosen as an objective. By means of a cross-sectional, descriptive, analytical, correlational and quantitative research approach. Twelve samples of matured goat milk cheeses were analyzed during 3 weeks, where each of these samples were subjected to special physicochemical methods such as: Kjeldahl method to obtain the percentage of protein and desiccation method to obtain the percentage of dry extract. The 12 samples corresponded to 2 brands obtained from 2 recognized supermarkets in the city of Guayaquil, Ecuador. The results obtained with the aforementioned methods were: protein 24.83% and dry extract 61.88%, results in accordance with the NTE INEN 2621 Standard first revision 2015-12. Matured goat milk cheeses. Requirements.
Keywords: Dry extract; goat's milk; protein; ripened cheeses